Effectiveness of a closed‐loop control system and a virtual educational camp for children and adolescents with type 1 diabetes: A prospective, multicentre, real‐life study. Issue 11 (2nd August 2021) - Cherubini, Valentino; Rabbone, Ivana; Berioli, Maria Giulia; Giorda, Sara; Lo Presti, Donatella; Maltoni, Giulio; Mameli, Chiara; Marigliano, Marco; Marino, Monica; Minuto, Nicola; Mozzillo, Enza; Piccinno, Elvira; et al.
Abstract: Aim: To evaluate the impact of a virtual educational camp (vEC) on glucose control in children and adolescents with type 1 diabetes using a closed‐loop control (CLC) system. Materials and Methods: This was a prospective multicentre study of children and adolescents with type 1 diabetes using the Tandem Basal‐IQ system. Insulin pumps were upgraded to Control‐IQ, and children and their parents participated in a 3‐day multidisciplinary vEC. Clinical data, glucose metrics and HbA1c were evaluated over the 12 weeks prior to the Control‐IQ update and over the 12 weeks after the vEC. Results: Forty‐three children and adolescents (aged 7‐16 years) with type 1 diabetes and their families participated in the vEC. The median percentage of time in target range (70‐180 mg/dL; TIR) increased from 64% (interquartile range [IQR] 56%‐73%) with Basal‐IQ to 76% (IQR 71%‐81%) with Control‐IQ ( P < .001). After the vEC, more than 75% of participants achieved a TIR of more than 70%. The percentage of time between 180 and 250 mg/dL and above 250 mg/dL decreased by 5% ( P < .01) and 6% ( P < .01), respectively, while the time between 70 and 54 mg/dL and below 54 mg/dL remained low and unaltered. HbA1c decreased by 0.5% ( P < .01). There were no episodes of diabetic ketoacidosis or severe hypoglycaemia. Conclusions: In this study of children managing their diabetes in a real‐world setting, more than 75% of children who participated in a vEC after starting a CLC system could obtain and maintain a TIR of more than 70%. The vEC was feasible and resulted in a significant and persistent improvement in TIR in children and adolescents with type 1 diabetes.